Social Consequences of the Global Financial Crisis in Latin America : Some Preliminary, and Surprisingly Optimistic, Conjectures - Ferreira, Francisco H.G.; Schady, Norbert (World Bank, Washington, DC, 2012)
Surprisingly, the most severe economic crisis the world has seen since the great depression does not appear to have had as dramatic an impact on poverty in Latin America as might have been expected. The exceptions to this heartening assessment are the countries geographically and economically closest to the United States, chiefly Mexico. Elsewhere, although poverty statistics for 2008-09 are not yet available, the data on output, unemployment and real wages suggest relatively modest changes in poverty. There are two candidate explanations for the smaller-than-expected increases in poverty in Latin America: lower output declines, deriving from enhanced protection against external shocks; and a lower output elasticity of poverty. If the latter is indeed observed when the required data becomes available, the report conjecture that it may reflect both the lower inflation rates now prevalent in the region, and recent reforms in the social protection system. For all their faults, the social protection systems in many Latin America and Caribbean (LAC) countries now reach the poor rather than only the middle-classes. The note concludes arguing against complacency, and pointing to areas where further research; and greater policy reform and experimentation are needed.